2006
DOI: 10.1186/bf03352007
|View full text |Cite
|
Sign up to set email alerts
|

A two-dimensional simulation of thermospheric vertical winds in the vicinity of an auroral arc

Abstract: The observations made by Fabry-Perot interferometers (FPIs), radars, and satellites have indicated that large vertical motion in the polar region is occasionally generated in the thermosphere associated with auroral activities. However, the behavior of the vertical wind is often very complicated, and the cause of the vertical wind has not been explained by auroral heating or by ion-neutral drag alone. It has been pointed out that a background horizontal flow is likely to significantly alter the dynamics of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 42 publications
0
32
1
Order By: Relevance
“…Sun et al, 1995;Shinagawa and Oyama, 2006) are inconsistent with the observation results shown here and from the FPIs. Most thermospheric-wind simulations show no significant variations in either vertical or horizontal winds below 120 km when the heating rate is at the same level as observed.…”
Section: A Physical Process For Generating Wind Variationscontrasting
confidence: 99%
“…Sun et al, 1995;Shinagawa and Oyama, 2006) are inconsistent with the observation results shown here and from the FPIs. Most thermospheric-wind simulations show no significant variations in either vertical or horizontal winds below 120 km when the heating rate is at the same level as observed.…”
Section: A Physical Process For Generating Wind Variationscontrasting
confidence: 99%
“…We compared with the ion temperature measured with the EISCAT radar, but clear increases were not identified for the time interval of the vertical-wind fluctuations. This may be because the measurement uncertainty of the EISCAT ion temperature at that time is almost equivalent to 20-30 K. We should note that a neutral temperature increase by a few degrees is enough to change the wind dynamics in the lower thermosphere (Sun et al, 1995;Shinagawa and Oyama, 2006). However, we are not sure if the increased thermal energy of ions is enough to elevate that of neutral particles or the neutral temperature.…”
Section: Theorymentioning
confidence: 80%
“…1. The Joule heating process increases the thermospheric temperature even at the lower thermospheric heights (Shinagawa and Oyama, 2006), and the temperature increase can directly affect the wind dynamics due to modification of the pressure gradient (Oyama et al, 2008;Tsuda et al, 2009). Therefore we investigate the temperature variations induced by the electric-field perturbations.…”
Section: Theorymentioning
confidence: 99%
“…The neutral atmosphere is treated as a nonhydrostatic compressible fluid, and the ionosphere is treated as a single-fluid collisional plasma. The modeling method of the neutral atmosphere is basically the same as that of Shinagawa and Oyama (2006). The simulation domain and basic configuration of the model are illustrated schematically in Fig.…”
Section: Simulation Modelmentioning
confidence: 99%